Some Forms of Stylistic Condensation in Newspaper English - Yeghyan, Anna (Armenian Folia Anglistika, 2008)
One of the underlying characteristic features of Newspaper English is its inclination towards stylistic condensation which is expressed at all levels - lexical, morphological, syntactic, stylistic, structural and ensures the realization of the core function of the Newspaper English – the informative function.